Development and Evaluation of Flurbiprofen Loaded Transethosomes to Improve Transdermal Delivery - Gadad, Anand Panchaxari; Patil, Archana Sidagouda; Singh, Yashica; Dandagi, Panchaxari Mallappa; Bolmal, Uday Baburao; Basu, Ananya (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Flurbiprofen is prescribed for the symptomatic management of arthritis. Its oral administration leads to gastrointestinal damage and it has a short elimination halflife requiring multiple dosing. Transdermal drug delivery of flurbiprofen is an alternative route to bypass the stratum corneum layer of the skin. Nano-vesicular carriers can be used to overcome this problem as it increases the permeability and skin deposition of the drug and reduces dosing frequency. Materials and Methods: Flurbiprofen loaded Transethosomes has been formulated by Thin-film hydration using Span 80 and Tween 80 as edge activators, Soyaphosphotidylcholine and varying percentage of ethanol. The vesicles were further characterized to study the effect of the type and concentration of edge activator and ethanol percentage on various parameters such as, particles size, polydispersity index, deformability index, entrapment efficiency and in-vitro drug release. A formulation having the least particle size, highest deformability index and best ex-vivo profile was optimized. The optimized formulation was dispersed in a gelling agent and evaluated for pH, drug content and compared with marketed formulation for ex-vivo permeation and skin deposition. Formulation containing Tween 80 in the ratio of 95:05 (Soyaphosphotidylcholine: Edge Activator) and having the highest ethanol percentage was optimized. Results and Discussion: On comparison with the marketed gel it was revealed that the optimized gel formulation containing higher concentration of Tween 80 had better ex-vivo profile and skin deposition. Conclusion: The formulated transethosomes may serve as potential carrier for effective management of arthritis.
Keywords: Flurbiprofen; Transethosomes; Thin film hydration method; Edge activator; Soyaphosphotidylcholine